Di Jalan Menuju Allah Dalam Terang St. Agustinus - Tan, Paulus Satyo Istandar (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2020)
If a person repents describing his journey to God then the journey has been completed. The story of his search was colored by the faith he embraced. But we may ask: what is the state of the person's soul, feelings and doubts, when searching? Or, how about the stages of the search? We can look for answers but ultimately it lies with the person concerned and we just need to believe, though we also keep calculating, the talk is certainly a trickle of faith.